Some notes on outro in Portuguese - Brugè, Laura; Giusti, Giuliana (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2021)
This paper studies the syntactic behavior of outro(s) in Brazilian and European Portuguese. Starting from the syntax of its Italian counterpart un altro/(degli) altri, we argue that outro(s) in prenominal position is neither an adjective nor a determiner, but an existential quantifier and that the presence of the indefinite article, um outro/uns outros, gives rise to a complex existential quantifier, like the corresponding Italian form. We also argue that outro(s) and um outro/uns outros do not specialize for different interpretations since they both substantially show the same ambiguity (one/some more or a/some different one(s)) and behave in the same way in relation to possible semantic interpretations typical of existential quantifiers.